2017
DOI: 10.1111/biom.12766
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Capture–Mark–Resight Estimation of Animal Population Density

Abstract: Sightings of previously marked animals can extend a capture-recapture dataset without the added cost of capturing new animals for marking. Combined marking and resighting methods are therefore an attractive option in animal population studies, and there exist various likelihood-based non-spatial models, and some spatial versions fitted by Markov chain Monte Carlo sampling. As implemented to date, the focus has been on modeling sightings only, which requires that the spatial distribution of pre-marked animals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 24 publications
1
68
0
Order By: Relevance
“…However, an unsolved problem remained: the requirement that the marked animals should be a random subset of the population (Royle et al, 2014). This requirement was overcome with advent of generalized SMR (Gen-SMR) models (Efford & Hunter, 2018;Whittington, Hebblewhite, & Chandler, 2017) which include sub-models for both marking and resighting processes. The model for the marking process describes the distribution of the marked individual, thereby relaxing the SMR assumption that marked and unmarked populations have the same spatial distributions and encounter probabilities (Whittington et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, an unsolved problem remained: the requirement that the marked animals should be a random subset of the population (Royle et al, 2014). This requirement was overcome with advent of generalized SMR (Gen-SMR) models (Efford & Hunter, 2018;Whittington, Hebblewhite, & Chandler, 2017) which include sub-models for both marking and resighting processes. The model for the marking process describes the distribution of the marked individual, thereby relaxing the SMR assumption that marked and unmarked populations have the same spatial distributions and encounter probabilities (Whittington et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(, Chap. 19) and with a complementary methods developed by Efford and Hunter (in press). In their analysis of rat ( Rattus rattus ) data, Efford and Hunter (in press) found that conventional SMR models underestimated density compared to generalized SMR models and that modelling resight data as counts or binary detections produced similar results.…”
Section: Discussionmentioning
confidence: 99%
“…19) and with a complementary methods developed by Efford and Hunter (in press). In their analysis of rat ( Rattus rattus ) data, Efford and Hunter (in press) found that conventional SMR models underestimated density compared to generalized SMR models and that modelling resight data as counts or binary detections produced similar results. Both their study and our study found that biases occurred even when marked animals were captured and marked on a regular grid of traps because the ratio of marked to unmarked animals decreased from the centre of the study area to the perimeter of the state‐space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations